Pengaruh Personal Attitude, Perceived Behavioral Control Terhadap Minat Berwirausaha Selama Pandemi Covid-19 Dimediasi Oleh E-Learning - Manggar Wulan Kusuma; Shita Lusi Wardhani (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2022)
The Covid-19 pandemic that hit the State of Indonesia has changed the way of learning in the field of education. Many universities are converting offline learning methods to online learning. This of course will affect the learning process of courses accompanied by business practices such as entrepreneurship courses. The purpose of this study was to examine the effect of personal attitude and perceived behavioral control in a person on entrepreneurial interest which will be mediated by the e-learning variable in the Covid-19 pandemic era. Data was collected through an online questionnaire that took entrepreneurship courses at selected universities in Yogyakarta. The data in this study were analyzed using SmartPLS software. E-learning is able to mediate personal behavioral control on interest in entrepreneurship, but unable to mediate personal attitude towards interest in entrepreneurship.